2010
DOI: 10.1098/rsta.2010.0008
|View full text |Cite
|
Sign up to set email alerts
|

Use of unnatural amino acids for design of novel organomodified clays as components of nanocomposite biomaterials

Abstract: Sodium montmorillonite (Na-MMT) clay was modified with three different unnatural amino acids in order to design intercalated clay structures that may be used for bone biomaterials applications. Prior work on polymer-clay nanocomposites (PCNs) has indicated the effect of the appropriate choice of modifiers on enhancing properties of PCNs. Our X-ray diffraction results indicate an increase in the d-spacing of Na-MMT clay after it was modified with the three unnatural amino acids. Transmission Fourier transform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 54 publications
0
42
0
1
Order By: Relevance
“…Detailed procedure of OMMT clay synthesis is described in our previous work [31]. Briefly, first, 5 g fine Na-montmorillonite (Na-MMT) powder was dispersed into 400 mL of deionized water pre-heated at 60°C.…”
Section: Synthesis Of Organically Modified Montmorillonite (Ommt) Claymentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed procedure of OMMT clay synthesis is described in our previous work [31]. Briefly, first, 5 g fine Na-montmorillonite (Na-MMT) powder was dispersed into 400 mL of deionized water pre-heated at 60°C.…”
Section: Synthesis Of Organically Modified Montmorillonite (Ommt) Claymentioning
confidence: 99%
“…The Altered Phase Theory of the PCNs was developed [28] that described that molecular interactions result in causing a ripple effect with influence on long range order of polymers and thus impact mechanical properties of PCNs. Based on the proposed model efforts were made to use nanoclays in design of biomaterials for bone regeneration [29][30][31][32][33]. We have used unique mineralization routes to mineralize hydroxyapatite inside nanoclays galleries for use in nanocomposites for bone tissue engineering [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Tailored side chains also allow new strategies in the search of a balance between mechanical properties and biocompatibility of several biomaterials: Katti et al reported an increased flexibility of montmorillonite-based bone cements after the introduction of amino acids with aliphatic side chains into the free volume between two adjacent layers. 51 Intercalation is not the only example of inorganic frameworks that can profitably host natural and unnatural amino acids, allowing possible future applications in life science: both UAAs and naturally occurring residues may be included 52,53 in the synthesis of metal-organic frameworks (MOFs) as organic ligands of the target metal ion/atom, an emerging class of materials, with a low density, a large surface area and an adjustable pore size. 54 In summary, the brief overview provided herein clearly describes the large amount interest that simple molecules, such as amino acids and their UAA analogues, continue to attract.…”
mentioning
confidence: 99%
“…The mixture was stirred for 24 h using the magnetic stirrer. Finally, the mixture was refluxed at 80 C for 6 h. 23 Afterward, the mixture was centrifuged for 2 h at 2000 rmin…”
Section: Modification Of Bentonite Clay (M-bet)mentioning
confidence: 99%